DEIXIS IN CHARLES DICKEN’S GREAT EXPECTATION - Mohamad Yunus Laia (Jurnal Education and Development, 2020)
This research aimed to know the types of deixis and how they used in the novel of Charles Dicken’s Great Expectation. The terms of deixis is not familiar to the learners of English although they use it both in spoken and written language. This research uses a descriptive qualitative approach. This research is categorized as descriptive qualitative research since the data are taken from words, phrases, and sentences based on deixis theory. Based on the data analysis and discussion are three types of deixis, they are person deixis, place deixis, and time deixis. Firstly, the result shows that person deixis dominates the most by means of emergences 207 times and the percentage is 67.21%. The person deixis is encoded by pronouns either plural or singular which reflect all characters in the novel and the referents could be speaker (first person), addressee (second person) and other participants (third person). In this novel, Pip, as the main character is highly often found since Dicken uses first- person point of view. Secondly, place deixis shows 58 times and the percentage is 18.83%. Demonstrative pronoun and adverb of place definitely encode place deixis which is centralized in and around England. Thirdly, time deixis appears the least from the others, it indicates 43 times and the percentage is 13.96%. Time deixis is symbolized by words and phrase adverb of time. Most referents of time deixis are past events.